Seismic flow units discretization and petrophysical modelling - Penna, Rodrigo Macedo (2024)
Rock typing into flow units (FU) is a well-known technique for characterizing flow heterogeneities in reservoirs and producing reliable estimations of petrophysical properties, as porosity and permeability. This thesis aims to discretize flow units in a Brazilian pre-salt reservoir through conventional core laboratory measurements and transpose this classification to the well log domain and 3D model of the reservoir, considering elastic and acoustic inverted seismic data as constraints. First, I performed core and well log data feasibility study of FU discretization, considering three different FU methods and the seismic vertical scale and resolution characteristics. This first study results provided means and grounds for the FU classification that I later chose to consider and the implications of the seismic limited vertical resolution in the classification. I noticed that porosity and permeability cumulative curves were a powerful tool for visualizing and analyzing the scale of the classification in a decametric sense, suitable for the seismic classification that the aim to achieve. The second study is a 3D FU Bayesian facies classification and petrophysical modeling considering the discretization made in the 1D domain. This is the first Brazilian pre-salt porosity and permeability 3D models constrained by both flow unit classification and elastic and acoustic inverted seismic data. The results from the second study showed that, using the FU as constraints, decametric porosity and permeability volumes are more robust in 3D approaches than considering the usual seismic lithologic classification. In the third study, I pushed the petrophysical modelling below the seismic vertical resolution, discretizing and calculating metric FU through geostatistical seismic inversion. Using the cumulative curve concept, I generated metric flow units within each decametric flow units and constrained the geostatistical inversion in this manner to generate several high-resolution porosity and permeability volumes with respect to the seismic data in the decametric scale. The results from the third generate high quality decametric and metric porosity and permeability volumes, respecting the available seismic data even below the resolution limit. Finally, I hope that the produced 3D volumes of flow units facies, permeability and porosity in decametric or metric scales can be incorporated as variables for the lateral interpolation of petrophysical reservoir parameters during the static and dynamic modelling, as well as support seismic 4D interpretations and seismic-assisted history matching.